The Jamaah Tabligh Movement in Indonesia: Peaceful Fundamentalist - Abdul Aziz (Studia Islamika, 2004)
The birth of Jamaah Tabligh was in fact a direct reaction to the emergence of aggressive Hindu proselytization movement, such as the Shuddhi (Purifying) and Sangathan (Consolidation) movement, which made wide-reaching attempt in the early 20th century to "return" to Hinduism those who had "left" the religion and converted to Islam during the period of Muslim political power in India. The main target of these right-wing Hindu movements were those they called "borderline Muslims" who still maintained many beliefs and cultural habit that had come from Hinuism. Maulana Muhammad Ilyas, founder of Jamaah Tabligh, believed that only a grass-roots Islamic movement could challenge the effort of Shuddhi and Sangathan, thought "purifying" these "borderline" Muslims and educating them about basic faith and worship in order to save them from the process of Hindunisation.DOI: 10.15408/sdi.v11i3.596